ARTIFICIAL INTELLIGENCE ENHANCES FLIPPED LEARNING ENVIRONMENTS FOR DEVELOPING B1-LEVEL LEARNERS’ PRODUCTIVE SKILLS - BEKTEMIROV, Zoir (The Lingua Spectrum, 2025)
The thesis aims to investigate how AI might enhance flipped learning settings, specifically in enhancing the productive skills of B1-level learners. This work examines the effectiveness of the flipped classroom model within student-centred foreign language teaching, with a particular focus on developing productive skills of B1-level learners. It further explores how Artificial Intelligence (AI) enhances flipped learning environments by providing personalized feedback, increasing learner autonomy, and improving overall communicative competence.